2012
DOI: 10.5430/jnep.v3n2p1
|View full text |Cite
|
Sign up to set email alerts
|

Health beliefs and practices related to pregnancy and childcare in Qatar: A qualitative study

Abstract: Purpose: The purpose of this study was to understand health beliefs and practices of Qatari women in the areas of pregnancy and childcare. Methods:A qualitative descriptive research design, using focus groups, was used in this study. Purposive sampling was used to recruit college age Qatari women from six universities in Qatar. A total of 43 Qatari women participated in this study. NVivo 8 qualitative analysis software was used to analyze the collected data.Results: A lack of knowledge about pregnancy and chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…Others who despite being pregnant for the first time, noted that they had already cared for their younger siblings and had some experiences in childcare practices. This is consistent with existing literature where there is documented evidence of the crucial role of the family, especially mothers in providing education on childcare to young mothers [ 32 ]. The childcare experiences of the teenage mothers were based on the use of common practices that were part of their family and community culture instead of scientific-based practices given by health professionals when caring for their babies [ 2 , 32 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Others who despite being pregnant for the first time, noted that they had already cared for their younger siblings and had some experiences in childcare practices. This is consistent with existing literature where there is documented evidence of the crucial role of the family, especially mothers in providing education on childcare to young mothers [ 32 ]. The childcare experiences of the teenage mothers were based on the use of common practices that were part of their family and community culture instead of scientific-based practices given by health professionals when caring for their babies [ 2 , 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with existing literature where there is documented evidence of the crucial role of the family, especially mothers in providing education on childcare to young mothers [ 32 ]. The childcare experiences of the teenage mothers were based on the use of common practices that were part of their family and community culture instead of scientific-based practices given by health professionals when caring for their babies [ 2 , 32 ]. Moreover, we observed that some teenage mothers used methylated spirit and cotton wool, while others used ‘traditional means’, such as, herbal medicine mixed with powder, palm kernel oil, shea butter, a hot towel that is heated from hot stone on the cord stump as a common way of cleaning and caring for the child’s umbilical cord.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Planning a pregnancy provides a dilemma for patients with RRMS and their physicians, in which the risks of active treatment must be balanced with the risks of relapse if treatment is withdrawn 73 . Cultural issues around pregnancy may be particularly problematic in Middle-Eastern countries such as Qatar, as there is a widespread preference for achieving pregnancy early in marriage, followed by raising large families, so that some Qatari women may spend a substantial period of their childbearing years in pregnancy 74 .…”
Section: Family Planningmentioning
confidence: 99%